Mapping the most problematic functions in chronic low back pain patients: Analysis of the patient-specific functional scale - ÖZEN BERKOL, TUĞÇE; KURU ÇOLAK, TUĞBA (My University, 2023)
Aim: Difficulty in functioning is one of the reasons by patients with low back pain (LBP) seek help. The purpose was to identify the problematic functions of chronic LBP patients using the Patient-Specific Functional Scale (PSFS) based on the International Classification of Functioning, Disability and Health (ICF) and investigate the related factors with the PSFS scores. Material and Methods: One-hundred LBP patients were included. The responses obtained from PSFS were linked to the ICF categories based on the linking procedure. Patient reported outcome measures (PROMs) and physical measurements were used for clinical assessment. Correlations were analyzed with Spearman’s rho correlation. Results: The identified 327 meaningful concepts were linked to 28 different 2ndlevel and 40 different 3rd level ICF categories. PSFS was found to correlate with the pain level during activity, perceived disability, and some domains of the health-related quality of life (p<0.05), while kinesiophobia and emotional status did not correlate with PSFS scores (p>0.05). Among physical tests, flexibility measurements correlated with PSFS scores (p<0.05). Discussion: Chronic LBP patients reported various functions. The content analyses showed the need for an extension of the ICF core sets for LBP. This study also revealed that not all PROMs and physical outcomes are able to reflect the difficulty level of the problematic activities. Assessment with PSFS may be beneficial for individually tailored treatment programs. Keywords Low Back Pain, ICF, PSFS, Rehabilitation
Keywords: Low Back Pain; ICF; PSFS; Rehabilitation